DIGITAL TRANSFORMATION THE FIRST STEPS OF VOICE OF VIETNAM (VOV) - Dong Manh Hung; Tran Huong Tra (CV KULTURA DIGITAL MEDIA, 2022)
Since its inception over a century ago, radio has proven to be one of humanity's most advantageous media. Radio has been modified to better serve the public as a result of the current technology revolution. The costs of starting a radio station with vast coverage are greatly decreased thanks to Internet broadcasting and streaming. The public can now readily listen to and even